A cascaded triple waist-enlarged taper few-mode fiber temperature sensor with beaded structure. (December 2022) - Fu, Xinghu; Huang, Zhexu; Li, Qiannan; Cao, Xiqing; Wang, Yufan; Fu, Guangwei; Jin, Wa; Bi, Weihong
Highlights: A cascaded triple waist-enlarged taper FMF temperature sensor is proposed. The sensor based on the beaded structure and FMF is sensitive to temperature. The beaded structure is formed by FMF and interferes with two modes. The temperature sensing characteristics of the sensor are analyzed. The temperature sensitivity is 89.41 pm/°C in 30–90 °C. Abstract: A cascaded triple waist-enlarged taper few-mode fiber (FMF) temperature sensor with beaded structure is proposed and fabricated. The main structure of the sensor is a waist-enlarged taper cascaded by multi-segment FMF. The diameter of the waist-enlarged taper structure affects the effective refractive index difference and therefore affects the sensitivity of the sensor. The effective refractive index difference of the sensor is 0.00199841. The diameters of the three waist-enlarged taper structures used in the experiment are 206.56 µm, 208.58 µm, and 208.58 µm. The function of the waist-enlarged taper cascaded structure is to couple the light transmission mode. Therefore, interference from other modes is reduced and the sensitivity of the sensor is improved. The experimental results show that in the range of 30–90 °C, the spectrum appears a red-shift phenomenon with the increase of temperature. The temperature sensitivity can reach 89.41 pm/°C, and there is a good linear relationship between wavelength shift and temperature change. The sensor has the advantages of simple structure, high sensitivity and good stability, it can be used for temperature detection in the fields of fire alarm, biomedicine and chemical sensing.